2017
DOI: 10.3390/app7020179
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Mode and Current-Mode Resistorless Third-Order Quadrature Oscillator

Abstract: This paper presents the realization of a resistorless third-order quadrature oscillator using two multiple-output current controlled current conveyor transconductance amplifiers (MO-CCCCTAs) and three grounded capacitors. The proposed circuit provides two quadrature voltage outputs, two high-impedance quadrature current outputs, and one high-impedance amplitude-controllable current output. The proposed oscillator satisfies the industrial requirement for amplifier and modulation signals and phase shift keying s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Basic concept of MO-CCCCTA Since the designed circuits are based on MO-CCCCTA, a concise description of MO-CCCCTA has been given in this section. Actually, MO-CCCCTA is a combined form of CCCII and OTA [27]. The schematic symbol and the equivalent circuit of the MO-CCCCTA have been displayed in Figures 1a and 1b, respectively.…”
Section: Circuit Description and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Basic concept of MO-CCCCTA Since the designed circuits are based on MO-CCCCTA, a concise description of MO-CCCCTA has been given in this section. Actually, MO-CCCCTA is a combined form of CCCII and OTA [27]. The schematic symbol and the equivalent circuit of the MO-CCCCTA have been displayed in Figures 1a and 1b, respectively.…”
Section: Circuit Description and Methodologymentioning
confidence: 99%
“…The multiple current output ports of the CCCCTA can be achieved easily by attaching additional current mirrors at the requisite output ports. In earlier literature, the MO-CCCCTA is shown to give a lot of flexibility in designing various analog signal processing circuits, such as oscillator [26][27][28], capacitance multiplier [29], inductance simulator [26,30], universal biquad filter [26,31], etc. However, to the best knowledge of the authors, no squaring or square-rooting circuit employing MO-CCCCTA has been reported so far in any open literature.…”
Section: Introductionmentioning
confidence: 99%
“…More attention is being given to electronically tunable components as traditional electronic components may have deviations in fine-tuning the tolerances of the electronic components [36]. Electronic tunability enhances the controllability of a microcomputer or microcontroller [37].…”
Section: Electronic Tunabilitymentioning
confidence: 99%
“…16,17,50 • A combination of an inverting lossy integrator with two lossless noninverting integrators in a loop. 15,[24][25][26] • A cascade connection of two noninverting lossy integrators and one lossless inverting integrator with unity feedback. 15,27,28 • A cascade connection of three lossy integrators in a unity negative feedback loop.…”
Section: Introductionmentioning
confidence: 99%